O ensino e aprendizagem de matrizes no contexto da resolução de problemas e da plataforma whatsapp - REIS, Michel Silva dos (Universidade Federal do Pará, 2018)
This research work was developed with the students of Youth and Adult Education - EJA of High School. The pedagogical organization in classes of this modality of acceleration of schooling can not have characteristic of common class, so I propose to develop with these students studies about the Matrices in two environments: the classroom for face meetings and the platform whatsapp for virtual meetings . The choice of the mathematic concept of matrices is justified by the fact that the students themselves show interest and relevance in their study, since the whatsapp application due to the fact of its popularization and familiarization among the researched students. In the face-to-face classes, the problem solving method was used to organize teaching. At the second moment, the students worked dialogically in the virtual group, seeking the development of the pedagogical activities presented, functioning as a discussion forum, guided by the teacher. The students interact by exchanging messages, sending answers to the questions raised, as well as doing researches and discussing the Matrix theme. In the quest to promote the teaching of mathematics from the use of media resources, we raise our research question: how to use whatsapp to promote learning autonomy, concept construction and student interaction with the mathematical concept from the media? To answer this question, I focus on the purpose of the research: to discuss the study of Matrices from Problem Solving, using whatsapp as the medium. The dialogues in the virtual group extend the students' time of study, through small comments and the theme flows to a conclusion, in addition to the student having in hand the record of the conversations and explanations of the teacher, in this sense the application whatsapp has direct impact in the proposal of this dissertation bringing an environment of revision and registration. In order to substantiate our proposal we dialogue with the authors who deal with: Matrizes, Guelli, Iezzi and Dolce ([198-?]); Problem Solving, Polya (2006); on the media, Lévy (1999), (2004), (2007), besides other researchers who collaborate in the discussions of the mentioned proposal. Reviewing the postings and the accumulation of information generated in the whatsapp environment in the Matrix study promotes a constant flow of information so that the student is not passive in front of them and develop their conclusions about the proposal presented by the teacher. The dynamic activities and tests with objective and discursive questions, worked in the classroom and in the virtual environment, will be part of the final product of this study, which aim to contribute to the improvement of students' performance in the learning activities of Mathematics.